The relationship between positive psychological capital and work engagement in clinical nurses: mediation effect of job crafting - Songran Park; Yeongmi Ha (BMC Nursing)
Abstract Background Nurses’ work engagement is critical for improving quality care, facilitating positive patient outcomes, and solving considering the nursing shortage. This study aimed to identify the mediating effect of job crafting on the relationship between positive psychological capital and work engagement in registered nurses. Methods A total of 132 hospital nurses with clinical experience of more than one year, excluding nurse administrators, participated. The participants were recruited from three hospitals in South Korea from August to September 2021. The SPSS 27.0 and PROCESS macro were used for data analysis. Results Positive psychological capital had a significant association with job crafting (β = 0.74, 95% CI = 0.71 to 0.95), and job crafting had a positive association with work engagement (β = 0.51, 95% CI = 0.29 to 0.56). In the mediating effect analysis, the mediating role of job crafting on the relationships between positive psychological capital and work engagement was statistically significant (β = 0.35, 95% CI = 0.24 to 0.48). Conclusions Based on our findings that positive psychological capital and job crafting could improve the work engagement of registered nurses, strengths coaching-based programs for increasing positive psychological capital and job crafting exercises for helping nurses make their job more engaging need to be developed.